(3ebOeI Edi GdOjebQGWjI GdEbJUGOjIs - (3QhHQJ(B, (3C(B.(3OGds ((3GdbGgQI(B:s (3GdOGQ GdOhdjI ddfTQ hGdJhRjY(B,s, 1998)
(3gd GdeSGhGI efGhFI ddMQjI?, GdOjebQGWjI, GdeSGhGI GdSjGSjI, hGdMQjI GdGbJUGOjI, GdOjebQGWjI hGdfXGe GdGbJUGOj, GdMb aj GdOjebQGWjI OGNd GdeDSSGJ, GdedcjI, hGdRYGeI, hGdeQMdI GdGfJbGdjIs
Keywords: (3GdELJeGY GdSjGSjs; (3GdMQjIs; (3GdOjebQGWjI GdGbJUGOjIs; (3GdeSGhGIs; (3GdedcjIs